Autonomy and choice in palliative care: time for a new model?. (10th October 2013) - Wilson, Fiona; Ingleton, Christine; Gott, Merryn; Gardiner, Clare
Abstract Aims This paper will examine understandings of autonomy and choice in relation to palliative and end‐of‐life care and identify implications for nursing practice. Background Autonomy in relation to patient‐centred care and advocacy has been identified as a key component of palliative and end‐of‐life care provision internationally. Understandings of autonomy have emerged in an individualised framework, which may be inadequate in supporting palliative and end‐of‐life care. Design A critical discussion paper. Data sources Seminal texts provide a backdrop to how autonomy is understood in the context of palliative care. An overview of literature from 2001 is examined to explore how autonomy and choice are presented in clinical practice. Implications for nursing A model of autonomy based on a 'decision ecology' model may be more applicable to palliative and end‐of‐life care. Decision ecology aims to situate the individual in a wider social context and acknowledges the relational dimensions involved in supporting choice and autonomy. Such a model recognizes autonomy around wider care decisions but may also highlight the everyday personal aspects of care, which can mean so much to an individual in terms of personal empowerment and dignity. Conclusion A 'decision ecology' model that acknowledges the wider social context, individual narratives and emphasises trust between professionals and patients may support decision‐making at end of life. Such a model must support autonomy not just at the level of wider decisions around care choice but also at the level of everyday care.